If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/5b+6=-6b+99
We move all terms to the left:
1/5b+6-(-6b+99)=0
Domain of the equation: 5b!=0We get rid of parentheses
b!=0/5
b!=0
b∈R
1/5b+6b-99+6=0
We multiply all the terms by the denominator
6b*5b-99*5b+6*5b+1=0
Wy multiply elements
30b^2-495b+30b+1=0
We add all the numbers together, and all the variables
30b^2-465b+1=0
a = 30; b = -465; c = +1;
Δ = b2-4ac
Δ = -4652-4·30·1
Δ = 216105
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-465)-\sqrt{216105}}{2*30}=\frac{465-\sqrt{216105}}{60} $$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-465)+\sqrt{216105}}{2*30}=\frac{465+\sqrt{216105}}{60} $
| 2(x-6)-6(x-2)=8-(x-4) | | 26x8= | | -3x-3(x-6)=-4(x+6) | | -23+-6n=49 | | -8-4(4m+6)=8(-2m-4) | | -6(y-5)=9y-30 | | 5w=9w+48 | | -2(6n-3)=-3(-2n-8) | | -1/3n-4=-20 | | -2(x=9)-11x=45 | | X(x+6)=45 | | -x-2=-1/2x-2 | | -(6y-5)=9y-30 | | 42.9+60z=49.95+25z | | X+15=10x | | -(-5p-5)=-23+p | | -2(5x+5)-3x+4=34 | | 3(g-4)=-3g | | -7(4x-9)+11=10(x-10)-54 | | 2n+15+4n+21=180 | | -4/5+x=-5/12 | | x+(2x-5)+(4x+11)=209 | | 2x-17+6=x | | 2x+4(x-5)=4(x-3) | | 3/2x+x=25 | | 6x-2=-8x-156 | | 12.5=tπ | | -16=2(x+9) | | 1/4x+1/3=5/12 | | x/2+-18=-35 | | 3(x-6)-6(x-3)=x+9(x-9) | | -0.5x^2+40x-350=2500 |